Munchausen Syndrome by proxy: Definition, context, and psychological factors involved - Gomes Gonçalves, Thomas (2014)
The Munchausen syndrome by proxy refers to a pathology characterized by physical and emotional abuse in which the simulation or production of symptoms is directed towards a child, which involves taking him or her to health treatments and unnecessary surgeries. The difficulties in the diagnosis of this form of abuse and the emotional aspects involved highlight the destructive effects in the infancy subjectivity due to the lack of loving capacity protecting and prioritizing the child demands. Psychoanalysis offers a differentiated view, comprehending that the mother attempts to elaborate her own psychic conflicts by the repetition of traumatic experience. There is a necessity of comprehension of the instinct destructivity presented in the maternal unconscious dynamics revealed in the modality of caring which is reflected in violence.